Dandy Walker variant mimicking as cerebral palsy with severe neurological impairment - Ghane, Vaishali Ramchandra; Patra, Kailash Chandra; Meshram, Narjohan; Chauhan, Arpan; Kalbhande, Anjali; Wankhede, Samir (International Journal of Research in Medical Sciences, 2017)
Dandy Walker Variant (DWV) is a less severe form of the spectrum of Dandy Walker Malformation (DWM). The DWM is a rare congenital intracranial posterior fossa malformation comprising cystic dilatation of the fourth ventricle, complete or partial agenesis of the cerebellar vermis and an enlarged posterior fossa. Clinically it presents with variable degrees of neurological impairment. Definitive diagnosis of DWM or DWV depends on neuroimaging as most of the clinical signs are not conclusive. This child was clinically suspected as spastic quadriplegic cerebral palsy had incidental finding of DWV on neuroimaging. Hence a definitive diagnosis of DWV was made by MRI in this case. Here we discuss the clinical and radiological aspects of this case with DWV without other associated anomalies yet presenting with clinically significant neurological impairment.